Evaluation of Education from the Perspective of the Hadiths of Al-Kutub As-Sittah - Acep Dani Ramdani; Nur Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Hadith is the second source of knowledge for Muslims after the Koran, the proof of a hadith needs to be explored so that it gives strength to the development of science because it really comes from the words, actions and taqrir of the Prophet Muhammad Saw.. In the context of education, especially evaluation, many hadiths are used as a basic source for developing evaluation. In the educational process, the way to find out how successful the learning objectives or participant competencies are is through evaluation. This research uses a literature review with a content analysis approach. Based on the findings of this research, several hadith histories were found which explain that the Prophet evaluated his friends in understanding religious teachings or in carrying out their duties, even the Prophet was also evaluated by Allah through the Angel Gabriel. The measurement system (measurement) used by the Prophet himself did not use a laboratory system, however the principles show that the measurement system is also found in the Hadith of the Prophet. Evaluation of education in Hadith pays attention to the quality of exams according to the religious level or level/class level. The domains of evaluation mentioned in the Hadith as the domains found in educational science today include: evaluation of the cognitive, affective and psychomotor domains.